Optimizing a tomato crocin biofactory by fine-tuning plant architecture - Lobato-Gómez, Maria; Fernández-Muñoz, Rafael; Orzáez, Diego; Granell, Antonio (Frontiers in Plant Science, 2026)
Tomato (Solanum lycopersicum) has emerged as a promising platform for the sustainable production of high-value metabolites. In this study, we demonstrate that plant architecture remodeling via genome editing can be exploited as a chassis optimization strategy in plant biofactories. Building on the previously established Tomaffron line, which accumulates saffron apocarotenoids in the fruit, and based on the established knowledge that mutations in SELF-PRUNING (SP) and SP5G genes generate compact, determinate tomato plants, we used CRISPR/Cas9 to edit the SP and SP5G genes in Tomaffron to improve crocin production. The resulting sp sp5g double mutants exhibited a compact growth habit combined with significantly higher fruit yield, total crocin content, and firmer ripe fruits compared with non-mutants. Remarkably, crocin yields per square meter increased nearly fourfold compared to non-mutant Tomaffron plants grown at the same density, representing progress toward achieving the crocin yields of Crocus sativus and offering the advantage of easier cultivation and harvesting in the tomato system. Our results show that genome editing of plant architecture is not only a tool for agronomic improvement but also a powerful strategy to fine-tune our tomato biofactory performance, offering a scalable and sustainable approach for the production of valuable metabolites.